2015
DOI: 10.1161/circulationaha.114.010835
|View full text |Cite
|
Sign up to set email alerts
|

Fat Embolism Syndrome

Abstract: The online-only Data Supplement is available with this article at http://circ.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
145
2
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(175 citation statements)
references
References 20 publications
2
145
2
26
Order By: Relevance
“…The biochemical theory or mechanism explains that destabilization of a plasma chylomicronemulsion lead stocoalescence off at stores. Subsequently, degradation of embolized fat into toxic intermediaries (free fatty acids and Creactive protein) results in the development of FES [9]. The incidence of FES ranges from <1 to 29% and it varies considerably according to the cause.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical theory or mechanism explains that destabilization of a plasma chylomicronemulsion lead stocoalescence off at stores. Subsequently, degradation of embolized fat into toxic intermediaries (free fatty acids and Creactive protein) results in the development of FES [9]. The incidence of FES ranges from <1 to 29% and it varies considerably according to the cause.…”
Section: Discussionmentioning
confidence: 99%
“…In short, mechanical embolism theory was thought that the fat particles in the venous circulation resulting the vascular blockage, pulmonary embolism and further, pulmonary hypertension, right heart failure, arteriovenous shunt and alveolar hypoperfusion. Biochemical damage theory believed that fat embolus in blood format glycerol and free fatty acids (FFA) and resulted the diffuse interstitial pneumonia, acute pulmonary edema, amplified inflammatory response and more serious, interstitial bleeding, edema, chemical pneumonia [3,7]. Thus, we are urgent to further investigate the real comprehensive mechanism of FES.…”
Section: Discussionmentioning
confidence: 99%
“…Fat embolism syndrome (FES), defined as fat within the circulation, happen after trauma, surgery and fat emulsion input and in other clinical conditions [1][2][3]. Documents reported that FES often occurred in non-traumatic patients, such as acute pregnancy fatty liver, heat stroke, alcoholism, sickle red blood cell anemia, liver necrosis and diabetes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory rate >30/min 1 to hypoxemia and fat embolism to the brain vessels (9). The pathophysiological mechanism of FES is still unclear, although there are some theories to explain the mechanism, such as the mechanical theory proposed by Gauss (1).…”
Section: Discussionmentioning
confidence: 99%